Protecting Industrial Control Systems. - Kirkpatrick, Keith (Communications of the ACM, 2019)
The article discusses the security risks associated with supervisory control and data acquisition (SCADA) systems. Particular attention is given to SCADA hacking prevention recommendations released by the U.S. National Institute of Standards and Technology (NIST).